2021
DOI: 10.1371/journal.pone.0258488
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of mandatory folic acid fortification of flours in prevention of neural tube defects: A systematic review

Abstract: Background Neural tube defects (NTDs) constitute the most frequent group among congenital malformations and are the main cause of neonatal morbimortality. Folic acid (FA) can reduce the risk of pregnancies affected by NTDs. Objective We aimed to investigate whether mandatory folic acid (FA) fortification of flours is cost-effective as compared to non-mandatory fortification, and to verify whether FA dosage, cost composition, and the quality of economic studies influence the cost-effectiveness of outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Unfortunately, it is difficult to reach the RDI of folates from one’s daily diet—especially for pregnant women and the elderly—without supplements. The mandatory fortification of folic acid—the man-made form of folates—in food has been applied in many countries and a significantly lower occurrence of folate-related disorders, such as neural tube defects, spina bifida, and encephalocele, was achieved [ 3 , 4 ]. However, reports of adverse health outcomes from excess intake of folic acid have aroused wide concern regarding this mandatory fortification [ 5 ], so developing food enriched with a natural form of folates is required.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it is difficult to reach the RDI of folates from one’s daily diet—especially for pregnant women and the elderly—without supplements. The mandatory fortification of folic acid—the man-made form of folates—in food has been applied in many countries and a significantly lower occurrence of folate-related disorders, such as neural tube defects, spina bifida, and encephalocele, was achieved [ 3 , 4 ]. However, reports of adverse health outcomes from excess intake of folic acid have aroused wide concern regarding this mandatory fortification [ 5 ], so developing food enriched with a natural form of folates is required.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review [ 15 ] of 13 cost-effectiveness studies of the mandatory FA fortification of flour found that FA dosages above 0.30 mg/100 g had a higher cost-effectiveness ratio and provided greater benefits (prevented cases and direct cost savings). This systematic review indicated a median return ratio of 17.5:1.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate a heavy economic burden of NTDs on health systems, which can be substantially reduced with preventive measures, such as flour fortified with FA [ 13 , 14 ]. Most economic analyses of the cost of these disorders have been conducted in the context of high-income countries, which tend not to reflect the economic burden of NTDs in low- and middle-income countries [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation faces many challenges as public health intervention, including that more than half the pregnancies on a global level are not planned [ 32 ], which makes it more challenging to consume the required supplements before conception. Therefore, large-scale FAFF has emerged as the most cost-effective intervention to improve folate status at the population level [ 7 , 33 ]. Currently, about 80 countries have mandatory FAFF programs [ 34 ], but few have monitored their effectiveness establishing proper quality assurance monitoring and evaluation practices, and even fewer have established appropriate NTDs surveillance systems or correlated these with folate determinations, both at the biological level and in the fortified foods.…”
Section: Discussionmentioning
confidence: 99%